Gender-specific effects of adverse childhood experiences on incidence of activities of daily life disability in middle-age and elderly Chinese population. (July 2021) - Yuan, Manqiong; Qin, Fengzhi; Zhou, Zi; Fang, Ya
Abstract: Background: Adverse Childhood Experiences (ACEs) may have long-lasting effects on late life health, probably through life-course mediators. However, whether such effects still exist when these mediators have been appropriately controlled is unclear. Objectives: To estimate the controlled direct effect of ACEs on Activities of Daily Life (ADL) disability in middle-aged people and examine the gender-difference of this effect. Participants and setting: We used data from the China Health and Retirement Longitudinal Study, a nationally representative longitudinal survey of persons aged 45+ years. Methods: ACEs were measured by the Adverse Childhood Experiences International Questionnaire and number of ACEs was classified as 0, 1, 2 and 3+, while ADL disability was measured using the Katz Index. Gender-specific controlled direct effects of ACEs on the incidence of ADL disability were estimated by marginal structural model (MSM) with stabilized inverse-probability-of-treatment weights of mediators (unhealthy behaviors, chronic diseases and depression). Results: 4, 544 males and 4, 767 females were included. Gender differences existed in most categories of ACEs, and about 10 % participants had 3+ ACEs. Participants who had 3+ ACEs had 39 % and 59 % higher risk of ADL disability than those with 0 ACEs among males and females, respectively. After controlling for the mediators, the direct effect was slightly increased in males (risk ratio (RR) = 1.45, p < 0.001) but decreased in females (RR=1.28, p < 0.05). Conclusions: Precautions targeted in reducing ACEs may be beneficial in preventing ADL disability, but gender-specific prevention should be considered.